LACK OF COLLABORATIVE GOVERNANCE IN BUILDING COMMUNITY DISASTER RESILIENCE - Oscar Radyan Danar; Tommy Anggriawan; Atsushi Suzuki; Asti Amelia Novita; Muhammad Rizki Pratama (DIA: Jurnal Administrasi Publik, 2021)
Many deaths and victims caused by catastrophic natural hazard occurred in Indonesia has proven the weakness of government to create a community disaster resilience among society. Under this circumstance any efforts of government are expected to be solution to stop or at least reduce the nightmare of society when the disaster occurred. This paper elaborates the discussion about building community disaster resilience through collaborative governance performed by Banyuwangi local government in Indonesia. Furthermore, the discussion about community disaster resilience and collaborative governance will be tied up by institutional and socio-ecological context. Therefore, this paper will highlight the role of actors, collaborative process and organization performance rather than any technical attributes from disaster resilience. The finding of this study reveals that there are some inhibiting factors influencing collaboration among actor to build community disaster resilience. The failure to manage these factors has resulting lack of collaboration and lead to weak community resilience in Banyuwangi.